Advancements in diagnostic solutions for complex viruses: an interview with Ralph Schimmer. (July 2018) - Greenway, Alice; Schimmer, Ralph
Ralph Schimmer, MD, MBA speaks to Alice Greenway, Commissioning Editor of Future Virology . Ralph has been Chief Medical Officer and Head Global Medical & Scientific Affairs for Centralized and Point of Care Solutions within the Roche Diagnostics division since May 2014. Between 2012 and 2016, Ralph was the Roche coordinator of the Innovative Medicines Initiative's (IMI) project Eu2P, a public-private partnership with a consortium of seven European universities, 15 pharmaceutical companies and the European and French Medicines Agencies. The Commissioning Editor of Future Virology, Alice Greenway, talks to Schimmer about the role that Roche Diagnostics plays in the development of tailored diagnostic solutions for complex viruses as well as the launch of the new Elecsys ® Zika IgG assay.